Polarized Variation - Kie Zuraw (Catalan Journal of Linguistics, 2016)
In cases of exceptionality, there are usually many words that behave regularly, a smaller number that behave irregularly (the exceptions), and perhaps an even smaller number whose behavior varies. This paper presents several examples of exceptionality and variation that are polarized in this way: most items exhibit one behavior or the other consistently, with only a minority of items showing variation. The result is a U-shaped histogram of behavior rates. In some cases, this requires listing of surprisingly long units. There are, however, some cases of bell-shaped histograms, where most items show variation, and only a minority are consistent. Some simple simulations are presented to show how polarized variation can result when variation is between two categorical outcomes, and both types of variation can result when variation is along a phonetic continuum.